UASB reactor effluent disinfection by ozone and chlorine - Ribeiro da Silva, Gustavo Henrique [UNESP]; Bruning, Harry; Gerrity, Daniel; Daniel, Luiz Antonio (Journal of Environmental Science and Health, 2015)
This research studied the sequential ozone and chlorine process with respect to, the inactivation of indicator bacteria and the formation of ozone disinfection byproducts in sanitary wastewater effluent. The applied ozone doses were 5, 8 and 10 mg.O3.L(-1), followed by chlorine doses of 10, 20 and 30 mg.L(-1), respectively. After the sequential ozone/chlorine process, the mean reduction in chemical oxygen demand ranged from 9 to 37%. Total coliform inactivation ranged from 1.59 to 3.73 log10, and E. coli was always <1 CFU 100 mL(-1). Ozonation resulted in the formation of aldehydes, which were not significantly impacted by the subsequent chlorine dose (P ≤ 0.05).
Keywords: Byproducts; Uasb reactor effluent; Chlorine; Disinfection; Ozone